Vliv 1-p-bromfenyl-5-merkapto-1,2,3,4-tetrazolu (Br FMT) na funkci stítné zlázy potkana - Nedvídková, J; Stolba, P; Strbák, V; Vanzura, J; Hrabálek, A; Vinsová, J (Ceskoslovenska farmacie, 1991)
The effects of the novel potential thyrostatic agent 1-p-bromphenyl-5- mercapto-1,2,3,4-tetrazole (Br-FMT) on the serum levels of thyroxine, thyrotropic hormone (TSH), the content of cyclic adenosine monophosphate (cAMP) in the thyroid gland, the body weight and the weight of the thyroid gland in liver transaminases and the white blood picture in Wistar strain rats were investigated. The effect of Br-FMT was compared with the effect of the well-known thyrostatic agent and goitrogen ethylester of 3-methyl-2-thio-4-imidazoline-1- carboxylic acid, carbimazole (Spofa) and with the control group, which received placebo only. The drugs tested were administered to animals in the dose do 7.5 mumol/animal via a gastric tube for the period of one month. Br-FMT and carbimazole decreased the level of serum thyroxine in a statistically significant manner. The serum level of TSH was evidently decreased after Br-FMT; it was not changed after administration of carbimazole in the given dose. The content of cAMP in the thyroid gland was significantly increased only after carbimazole. The weight of the thyroid gland was not significantly changed in any group under study, though after carbimazole the mean value was higher by a quarter as compared with the control group. The body weight and white blood picture were not significantly changed in all groups under study. ALT and AST values were evidently lower after carbimazole and Br-FMT, most probably due to the hypothyroid state of the animals.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Tetrazoles; karbimazol; thyroxin; Rats; tetrazoly; Rats, Inbred Strains; AMP cyklický; Thyroid Gland; Animals; Thyrotropin; Carbimazole; krysa rodu Rattus; thyreotropin; Thyroxine; zvířata; Cyclic AMP; inbrední kmeny potkanů; štítná žláza